2013
DOI: 10.1152/ajpheart.00819.2012
|View full text |Cite
|
Sign up to set email alerts
|

Human-induced pluripotent stem cell-derived cardiomyocytes exhibit temporal changes in phenotype

Abstract: Human-induced pluripotent stem cell-derived cardiomyocytes (hiPS-CMs) have been recently derived and are used for basic research, cardiotoxicity assessment, and phenotypic screening. However, the hiPS-CM phenotype is dependent on their derivation, age, and culture conditions, and there is disagreement as to what constitutes a functional hiPS-CM. The aim of the present study is to characterize the temporal changes in hiPS-CM phenotype by examining five determinants of cardiomyocyte function: gene expression, io… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
112
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(122 citation statements)
references
References 69 publications
7
112
1
Order By: Relevance
“…Color images available online at www.liebertpub.com/adt we have shown that whole-cell recordings with high GO seal resistances can be obtained reproducibly with the CytoPatch 2 equipment, and that cardiac AP can be induced and recorded, offering comparable results with those obtained in manual patch-clamp studies. 22,[28][29][30] In particular it is possible to characterize and quantify cell fractions in terms of the quantitative features of the AP, that is, to distinguish between atrial, nodal, and ventricular types of AP, and to determine the yield of successful recordings. In this respect, it was encouraging for us to find proportions of ventricular, atrial, and nodal CMs, according to AP morphology, [30][31][32][33] as well as quantitative AP parameters, 28,30-36 similar to those reported in previous electrophysiology studies on stem-cell-derived CM preparations.…”
Section: Discussionmentioning
confidence: 99%
“…Color images available online at www.liebertpub.com/adt we have shown that whole-cell recordings with high GO seal resistances can be obtained reproducibly with the CytoPatch 2 equipment, and that cardiac AP can be induced and recorded, offering comparable results with those obtained in manual patch-clamp studies. 22,[28][29][30] In particular it is possible to characterize and quantify cell fractions in terms of the quantitative features of the AP, that is, to distinguish between atrial, nodal, and ventricular types of AP, and to determine the yield of successful recordings. In this respect, it was encouraging for us to find proportions of ventricular, atrial, and nodal CMs, according to AP morphology, [30][31][32][33] as well as quantitative AP parameters, 28,30-36 similar to those reported in previous electrophysiology studies on stem-cell-derived CM preparations.…”
Section: Discussionmentioning
confidence: 99%
“…15, 52 By contrast, although the I Ca,T current has been found in a subset of cells, its properties have not defined. 55 …”
Section: Electrophysiological Phenotypes and Ion Channel Functionmentioning
confidence: 99%
“…nodal CM[10]. These differences in ion channel expression between sam-205 ples from human ventricles and hiPSC-CM argue again for a mixed pop-206 ulation of ventricular, atrial and nodal-like CM after differentiation.…”
mentioning
confidence: 96%